2022
DOI: 10.21470/1678-9741-2020-0635
|View full text |Cite
|
Sign up to set email alerts
|

Bioprosthetic Aortic Valve Degeneration: a Review from a Basic Science Perspective

Abstract: Introduction The increase in the prevalence of aortic stenosis due to an aging population has led to an increasing number of surgical aortic valve replacements. Over the past 20 years, there has been a major shift in preference from mechanical to bioprosthetic valves. However, despite efforts, there is still no "ideal" bioprosthesis. It is crucial to understand the structure, biology, and function of native heart valves to design more intelligent, strong, durable, and physiological heart valve tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…This study contributes to highlighting the potential role of HSA oxidative modifications as a marker of oxidative stress in patients with aortic valve stenosis, a multifactorial process, including chemical, mechanical, and immunological factors. Although the contribution of each mechanism remains poorly understood, it represents an active field of investigation [32,60,61]. In this study, we showed that patients with a severe valvular disease that required surgical intervention with replacement of the aortic valve had higher oxidative stress compared to control subjects evidenced by an increase in HSA-Cys, the oxidized form of HSA, and a concomitant decrease in the reduced form (HSA-SH).…”
Section: Discussionmentioning
confidence: 68%
“…This study contributes to highlighting the potential role of HSA oxidative modifications as a marker of oxidative stress in patients with aortic valve stenosis, a multifactorial process, including chemical, mechanical, and immunological factors. Although the contribution of each mechanism remains poorly understood, it represents an active field of investigation [32,60,61]. In this study, we showed that patients with a severe valvular disease that required surgical intervention with replacement of the aortic valve had higher oxidative stress compared to control subjects evidenced by an increase in HSA-Cys, the oxidized form of HSA, and a concomitant decrease in the reduced form (HSA-SH).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, these valves are coated with a thin layer of turbostratic carbon (CarboFilm), which improves biocompatibility and encourages endothelialization. Although these leaflet processing methods are theoretically proposed to avert bioprosthetic dysfunction, their long-term effects are still largely unexplored [16,17]. Despite the scarcity of research in this area, it is hypothesized that these leaflet preservation techniques might, for various reasons, play a role in the onset of thrombocytopenia.…”
Section: Jcsmentioning
confidence: 99%
“…Xenoantigens, mainly 𝛼-Gal antigens, mediate the production of anti-𝛼-Gal antibodies in the host, which stimulate the infiltration of inflammatory cells, the secretion of matrix metalloproteinases, and the breakdown of the extracellular matrix, leading to structural degradation manifested by leaflet tears, destruction, leaflet retraction, and secondary hemodynamic disturbances. [102,103] 4) Glycation: This refers to a complex constellation of chemical reactions between saccharides and side chains of the molecules such as lysine and arginine residues. Biochemical modification of the extracellular matrix, such as glycation has been reported to lead to biomechanical stiffening and structural dysfunction.…”
Section: Structural Valve Degenerationmentioning
confidence: 99%
“…Although BHVs mimic the natural valves as much as possible in terms of structure and function, the endothelial cells and mesenchymal cells in natural heart valves are completely removed as a result of the preparation and processing such as cross‐linking and fixation of the BHVs, and the toxicity of glutaraldehyde remaining in BHVs prevents endothelial cells from colonizing and growing. [ 103 ] As a result, BHVs are difficult to re‐endothelialize during the early implantation period and due to the absence of active cells, thus lacking the self‐repairing and remodeling ability of native heart valves. The layers of endothelial cells play an essential role in cardiovascular systems as natural barriers between blood and tissue.…”
Section: The Defects Of Bioprosthetic Heart Valves and Clinical Outcomesmentioning
confidence: 99%